Pengaruh Managerial Ownership, Sales Growth, ROA, dan Cash Holding terhadap Manajemen Laba - Anita Himawati; Waskito, Jaka; Hapsari, Ira Maya (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Earnings management is a crucial topic in the business world because it can impact the reliability of financial reports and the economic decisions of stakeholders. This practice is often employed to provide a better picture of financial conditions. This study aims to examine the influence of managerial ownership, sales growth, ROA, and cash holdings on earnings management in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative approach was used with secondary data obtained from the official IDX website. From a total population of 94, 24 samples were selected using a purposive sampling technique. Data analysis was carried out using multiple linear regression using SPSS version 25. The results showed that partially managerial ownership (tcount 0.164 < ttable 1.97769; sig. 0.870 > 0.05) and sales growth (tcount -0,907 > -ttable -1.97769; sig. 0.366 > 0.05) can be concluded as having no effect on earnings management, while ROA (tcount 6.436 > ttable 1.97769; sig. 0.000 < 0.05) and cash holding (tcount -4.481 < -ttable -1.97769; sig. 0.000 < 0.05) can be concluded as having an effect on earnings management. Simultaneously, these four variables have an effect on earnings management (Fcount of 12.347 > Ftable 2.67 and sig. value 0.000 < 0.05).